Western blotting using Strongyloides ratti antigen for the detection of IgG antibodies as confirmatory test in human strongyloidiasis - Silva,Luciana Pereira; Barcelos,Ivanildes Solange da Costa; Passos-Lima,Andréia Barcelos; Espindola,Foued Salmen; Campos,Dulcinéa Maria Barbosa; Costa-Cruz,Julia Maria (Instituto Oswaldo Cruz, Ministério da Saúde, 2003)
The present study was conducted to evaluate the frequency of antigenic components recognized by serum IgG antibodies in Western blotting (WB) using a Strongyloides ratti larval extract for the diagnosis of human strongyloidiasis. In addition, the WB results were compared to the enzyme-linked immunosorbent assay (ELISA) and the indirect immunofluorescence antibody test (IFAT) results. Serum samples of 180 individuals were analyzed (80 with strongyloidiasis, 60 with other intestinal parasitoses, and 40 healthy individuals). S. ratti was obtained from fecal culture of experimentally infected Rattus rattus. For IFAT, S. ratti larvae were used as antigen and S. ratti larval antigenic extracts were employed in WB and ELISA. Eleven S. ratti antigenic components were predominantly recognized by IgG antibodies in sera of patients with strongyloidiasis. There was a positive concordance for the three tests in 87.5% of the cases of strongyloidiasis. The negative concordance in the three tests was 94% and 97.5%, in patients with other intestinal parasitoses and healthy individuals, respectively. In cases of positive ELISA and negative IFAT results, diagnosis could be confirmed by WB. ELISA, IFAT, and WB using S. ratti antigens showed a high rate of sensitivity and specificity. In conclusion, WB using S. ratti larval extract was able to recognize 11 immunodominant antigenic components, showing to be a useful tool to define the diagnosis in cases of equivocal serology.